AN ANALYSIS OF MORPHOLOGICAL PROCESSES ON THE WORDS CONTAINING DERIVATIONAL AFFIXES IN EDGAR ALLAN POE’S THE BLACK CAT - Herlina, Nurul Ika; Kholiq, Muh. (UG Journal, 2020)
This research aims to analyze Morphological processes on the words containingderivational affixes in Edgar Allan Poe’s The Black Cat. The method of this researchis descriptive qualitative. The researcher found 154 words that attached by derivationalaffixes as the result of this research. They can be categorized based on part of speechinto four types: the first is derivational affixes producing noun. They have percentage45%, with the suffixes-ence, -cy, -ty, -ity, -tion, -ation, -ion,-ment, -ure, -ness, -ent, -ance ,-er, -or, and -ing. The second is derivational affixes producing verb. Theyhavepercentage 1%, with the suffix -en. The third is derivational affixes producingadjective. They have percentage 17%, with the suffixes -al, -able, -ful, -y, -ish, -ent,-less, -ing and -ous. The last is derivational affixes producing adverb. They havepercentage 37%, with the suffix –ly. The researcher also found the prefixes, they areun-,in-,dis- and re-. The derivational affixes producing noun is the most frequentlyappear in Edgar Allan Poe’s The Black Cat with a percentage of 45%.